In-situ crystallization high zeolite waste plastic catalytic cracking microsphere catalyst and preparation method and application thereof

By catalyzing the microsphere catalyst of high zeolite waste plastic in situ crystallization, the problem of low yield of low carbon olefins in existing catalysts is solved, especially the yield of propylene, and efficient catalytic cracking is achieved to produce chemicals such as ethylene, propylene and butene, which improves the activity and stability of the catalyst.

CN119702056APending Publication Date: 2025-03-28SHANDONG UNIV OF TECH

Patent Information

Application Number
CN202411599166.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the process of producing low-carbon olefins, the yield of low-carbon olefins, especially propylene, needs to be further improved.

Method used

In situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst is used. This catalyst can efficiently catalytically crack the waste plastic into one-step and produce chemicals such as ethylene, propylene and butene through nano-zolized ZSM-5 zeolite content, good wear resistance and strong hydrothermal stability.

Benefits of technology

Maximize the yield of low-carbon olefins, especially propylene, which significantly improves the yield. At the same time, the liquid products are rich in aromatic hydrocarbons, which improves the reactivity and service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an in-situ crystallization high zeolite waste plastic catalytic cracking microsphere catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalyst materials. Carrying out spray drying on mixed slurry consisting of clay, an external silicon source, the pre-crystallization liquid and water to obtain microspheres; the preparation method comprises the following steps: preparing microspheres, roasting the microspheres, mixing the roasted microspheres with an alkali-containing aqueous solution and a template agent to obtain a mixture, carrying out hydrothermal crystallization, filtration and separation on the mixture, adding a phosphorus compound and a metal compound into a product obtained after hydrothermal crystallization, uniformly mixing, and carrying out drying and roasting treatment to obtain the in-situ crystallization high-zeolite waste plastic catalytic cracking microsphere catalyst. The in-situ crystallization nanocrystallization ZSM-5 catalyst is high in zeolite content and developed in mesopores, and the molecular sieve and the matrix are tightly combined through similar chemical bonds, so that the activity stability of the catalyst is enhanced; the catalyst is used for catalytic cracking reaction of waste plastics, is high in reaction activity and long in service life, greatly improves the yields of ethylene, propylene and butylene, and is rich in aromatic hydrocarbons in liquid products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst materials, and in particular relates to an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst, a preparation method and an application thereof. Background Art

[0002] Urban solid waste, mainly waste plastics, is increasingly affecting human life and the ecological environment. According to statistics, the global output of plastic products in 2020 was 367 million tons, of which my country accounted for about 30%. It is estimated that by 2050, all kinds of plastic waste in the natural environment and landfills will reach 12 billion tons. Although waste plastics are garbage, they are also a good resource of carbon and hydrogen. Compared with various waste plastic treatment methods, the production of light oil products and low-carbon olefins through catalytic thermal cracking is the most promising technology. The catalyst has the function of reducing the activation energy of the reaction and adjusting the product distribution. It is the technical key of this process method. For this purpose, various catalytic materials and cracking catalyst preparation methods have been studied and developed.

[0003] CN116371455A discloses a catalyst for cracking waste plastics, comprising a high-temperature calcined rare earth MOFs coated modified ZSM-5 molecular sieve, wherein the rare earth MOFs account for 0.1-40% of the catalyst, effectively increasing and enriching the catalyst active sites, which is conducive to improving the conversion efficiency of macromolecular plastics and reducing the coke yield. The catalyst is used in the catalytic cracking process of waste plastics, which improves the yield of liquid products, but the yield of low-carbon olefins is not high.

[0004] CN117623329A discloses a dual-pore composite molecular sieve and a preparation method thereof, wherein the dual-pore composite molecular sieve comprises a SAPO-5 molecular sieve and a cubic single crystal all-silicon mesoporous molecular sieve, wherein the former accounts for 50-74% and the latter accounts for 26-50%. The composite molecular sieve can be directly used for catalytic cracking reaction of waste plastics, increasing the production of certain low-carbon olefins, but does not specify the yield of propylene.

[0005] CN117654607A discloses a dual-channel composite catalyst for catalytic cracking of waste plastics to produce low-carbon olefins and its preparation method, the catalyst contains a modified ZSM-35 molecular sieve and a short rod-shaped mesoporous molecular sieve, wherein the ZSM-35 is loaded with boron oxide and metal oxides accounting for 46-70%; the short rod-shaped mesoporous molecular sieve accounts for 30-54%. The composite molecular sieve catalyst is used for the cracking of waste plastics with limited low-carbon olefin yield.

[0006] CN12316986A discloses a catalyst for cracking waste plastics to generate low-carbon olefins and aromatics. The raw materials of the catalyst include a heat carrier, first to third active components, the heat carrier contains at least one oxide of silicon, aluminum, alkali metal and alkaline earth metal, the first active component contains at least one oxide of Zn, Cu, Ni, Mn, La, Ce and Ti, the second active component includes an oxide of alkali metal and / or alkaline earth metal, and the point active component is selected from at least one oxide of Zn, Ga, P, Cr, Ag and K. The catalyst is inexpensive, but the yield of low-carbon olefins is relatively low.

[0007] CN113398982A discloses a catalyst for preparing low-carbon olefins from waste plastics, comprising a silicon-aluminum matrix and a molecular sieve, wherein the matrix based on silicon oxide accounts for 10-40% of the catalyst, and the mechanism based on aluminum oxide accounts for 30-60% of the catalyst; the molecular sieve includes ZSM-5 molecular sieve and / or ZSM-11 molecular sieve, accounting for 10-40% of the catalyst. The catalyst has a high yield of liquefied gas for cracking waste plastics, but a relatively low yield of propylene.

[0008] CN116371458A discloses a high zeolite nano ZSM-5 microsphere catalyst and its preparation method. The present invention extracts part of aluminum oxide and impurities from the first clay skeleton by acid extraction of clay raw materials, thereby increasing the skeleton silicon-aluminum ratio, improving the pore structure, and enabling the remaining SiO2 to be pre-activated, which is beneficial to the subsequent in-situ growth of ZSM-5. The catalyst has a high ZSM-5 content and well-developed mesopores. It can be used in the catalytic cracking reaction of hydrocarbon substances to greatly increase the yield of low-carbon olefins and improve the octane number of gasoline.

[0009] CN116371459A discloses a catalytic cracking catalyst and a preparation method thereof. Acid-extracted clay and pre-crystallization liquid are added to the raw materials for preparation, and the catalyst is prepared by in-situ crystallization molecular sieve technology. The prepared catalytic cracking catalyst has a high ZSM-5 zeolite content, small crystals, good microsphere abrasion resistance, and high MAT micro-reaction activity. It is used for catalytic cracking reactions of petroleum hydrocarbons and can greatly improve the diene yield.

[0010] CN116240042A discloses a method and device for producing olefins by catalytic cracking of waste plastics. The method comprises mixing heated and molten waste plastics with recycled cracking oil and then performing a catalytic cracking reaction under the action of a microsphere catalyst, regenerating the catalyst after the reaction, separating the reaction products to obtain low-carbon olefin products and cracking oil products, and partially recycling the cracking oil. The catalyst of this method can directly crack waste plastics to produce low-carbon olefins.

[0011] CN117244583A discloses a cracking catalyst and a preparation method thereof, comprising a composite carrier and a modified oxide, wherein the composite carrier comprises 8-32% hydrogen-type Y molecular sieve and 54-90% KIT-6 all-silicon mesoporous molecular sieve, and the modified oxide accounts for 2-14%. The catalyst has a low yield of light olefins in the catalytic cracking reaction of waste plastics.

[0012] CN116493039A discloses a catalyst for catalytic cracking of waste plastics to produce olefins, and its preparation method and application. The catalyst comprises 41-65% ZSM-5 molecular sieve, 3-9% second active component, and 1-9% auxiliary active component. The catalyst can effectively catalytically crack waste plastics to produce chemicals such as ethylene, propylene and butene in one step, and has the characteristics of strong anti-deactivation ability and effective removal of chlorides.

[0013] It can be seen that in the existing technology of producing light olefins using catalytic cracking catalysts from waste plastics, the yield of light olefins, especially propylene, needs to be further improved. Summary of the invention

[0014] In view of the problem of low yield of low carbon olefins in the existing technology of preparing low carbon olefins by catalytic cracking catalysts of waste plastics, the present invention provides an in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst and a preparation method and application. The catalyst has the characteristics of high content of nano-ZSM-5 zeolite, good abrasion resistance and strong hydrothermal stability. It can efficiently catalytically crack waste plastics to produce chemicals such as ethylene, propylene and butene in one step, and can maximize the yield of low carbon olefins.

[0015] The present invention is achieved through the following technical solutions: A method for preparing an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst comprises the following steps: (1) spray drying a mixed slurry consisting of clay, an additional silicon source, a pre-crystallization liquid and water into microspheres; (2) calcining the microspheres in step (1), mixing the calcined microspheres with an alkaline aqueous solution and a template to obtain a mixture, subjecting the mixture to hydrothermal crystallization, filtering, and separating, adding a phosphorus compound and a metal compound to the hydrothermal crystallization product, mixing well, and then drying and calcining to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst.

[0016] Furthermore, the clay in step (1) includes acid-extracted clay and natural clay; the mixed slurry includes the following raw materials in parts by weight: 5-80 parts of acid-extracted clay, 5-70 parts of natural clay, 10-70 parts of an added silicon source, and 0.5-20 parts of a pre-crystallization liquid; the solid content of the mixed slurry is 25-65%.

[0017] Furthermore, the clay in step (1) includes acid-extracted clay and natural clay; the mixed slurry includes the following raw materials in parts by weight on a dry basis: 10-70 parts of acid-extracted clay, 10-60 parts of natural clay, 15-65 parts of an added silicon source (silicon dioxide on a dry basis), and 1-18 parts of a pre-crystallization liquid; and the solid content of the mixed slurry is 30-60%.

[0018] Furthermore, the clay is one or more of kaolin, halloysite, diatomaceous earth, bentonite, montmorillonite, attapulgite, pyrophyllite and perlite; the added silicon source is one or more of white carbon black, silicone grease, silica gel, silica sol and water glass; the preparation method of the acid-extracted clay is: at 40-150°C, the clay powder is placed in an acid solution for 0.3-8h, and then alkali is added to adjust the pH value of the system to 1.0-7.5; the preparation method of the pre-crystallization solution is: the template, aluminum source and silicon source are mixed evenly, and then crystallized at 80-250°C for 2-48h to obtain the pre-crystallization solution.

[0019] Furthermore, the acid solution is one of 0.5-12M hydrochloric acid, sulfuric acid, nitric acid and orthophosphoric acid solutions, and the mass ratio of the acid solution to the clay powder is 1.5-10:1; the clay powder is clay powder calcined at 500-950°C for 0.1-8h; the alkali is ammonia water; the template is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine, triethylamine, diethylammonium and ammonia water; the aluminum source is one or more of pseudoboehmite, boehmite, sodium aluminate, aluminum sulfate, aluminum nitrate and aluminum chloride; the silicon source is one or more of white carbon black, silicone grease, silica gel, silica sol and water glass; the molar ratio of the template, aluminum source and silicon source is 0.005-0.5:1:10-150.

[0020] Furthermore, the alkali in the alkaline aqueous solution in step (2) is one or more of sodium hydroxide, sodium aluminate, water glass, and ammonia water; the template agent is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine, triethylamine, diethylammonium, and ammonia water; the phosphorus compound is one or more of phosphoric acid, phosphorous acid, ammonium phosphate, diammonium phosphate, and diammonium hydrogen phosphate; and the metal compound is one or more of lanthanum, cerium, titanium, iron, cobalt, silver, zinc, vanadium, and copper compounds.

[0021] Furthermore, the SiO2 in the calcined microspheres reacts with the alkali aqueous solution OH -The molar ratio of SiO2 to template in the microspheres after calcination is 1:0.01-1.0; the mass ratio of the dry basis of the product after hydrothermal crystallization to the phosphorus-containing compound calculated as P2O5 and the metal compound calculated as metal oxide is 1:0.005-0.1:0.01-0.15.

[0022] The metal compound is one or more of calcium, magnesium, strontium, lanthanum, cerium, titanium, iron, cobalt, chromium, silver, zinc, vanadium, copper, manganese, gallium and molybdenum compounds.

[0023] Furthermore, the microspheres in step (2) are calcined at 500-1200°C for 0.5-8h; the hydrothermal crystallization is at 100-250°C for 5-40h; and the calcination of the crystallized product is at 400-700°C for 0.5-4h.

[0024] In the present invention, the in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst prepared by the preparation method is used.

[0025] In the present invention, the in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst is used in catalytic cracking of waste plastic.

[0026] The in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst prepared by the present invention is used for the direct catalytic cracking process of waste plastic to produce light oil products and low-carbon olefins; the waste plastic catalytic cracking process refers to directly mixing the in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst with waste plastic powder in a fluidized bed reactor, at a reaction temperature of 350-700°C (preferably 400-650°C), a catalyst-oil ratio of 3-30 (preferably 5-25), and a reaction time of 0.3-10s (preferably 0.5-8s). After the reaction, the catalyst and the product are separated, the cracked heavy oil component enters the reaction system to continue the reaction, and the catalyst to be regenerated enters the regenerator for charring and resurrection treatment, and then enters the reactor for cyclic reaction.

[0027] Beneficial Effects The in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst prepared by the present invention has a high zeolite content and a well-developed mesopore. The molecular sieve is tightly combined with the matrix by a similar chemical bond, thereby enhancing the activity and stability of the catalyst. The in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst is used for catalytic cracking reaction of waste plastics. Due to the synergistic effect of the high-zeolite nano-ZSM-5 and the metal complex, it has the characteristics of high reaction activity and long service life, greatly improving the yields of ethylene, propylene and butene, and the liquid product is rich in aromatics. DETAILED DESCRIPTION

[0028] The present invention is further described below with reference to the examples, but these examples are not intended to limit the present invention (all examples are based on dry basis unless otherwise specified).

[0029] The parts in the following examples are parts by weight.

[0030] 1. Analytical test methods (1) ZSM-5 content determination: X-ray diffraction method, measure the XRD spectra of the sample and the standard sample at 2θ of 22.5-25 o The sum of the peak areas of the five characteristic diffraction peaks between the two is the percentage value of the ZSM-5 content; the standard sample is the high-quality ZSM-5 molecular sieve produced by Nankai University, and its crystallinity is set at 95%; (2) Determination of active SiO2 in clay: During the high-temperature calcination of microspheres, part of SiO2 remains in an amorphous state and can be converted into zeolite during the hydrothermal crystallization process. This part of SiO2 is called active SiO2. The determination method is as follows: weigh 5g of sample and put it into a conical flask, add 25mL of 15% sodium hydroxide solution, then extract it in a water bath at 80℃ for 1h with intermittent shaking, then filter it, rinse the solid product with 0.5mol / L sodium hydroxide solution, transfer the filtrate into a 250mL volumetric flask, add 0.5mol / L sodium hydroxide solution to dilute to the scale, and then analyze and titrate the percentage of SiO2 in the weight of clay, which is the content of active SiO2. (3) Determination of clay active A12O3: weigh 5g sample and put it into a 250mL conical flask, add 36.8mL of 6mol / L hydrochloric acid solution, extract in a constant temperature water bath at 80 degrees for 80 minutes, then filter, wash three times with 150mL of 60℃ 0.5mol / L hydrochloric acid solution, finally collect the filtrate in a 250mL volumetric flask, titrate and analyze the percentage of A12O3 content in the weight of clay, which is the active A12O3 content; (4) Kaolinite and halloysite: X-ray diffraction method; elemental composition and silicon-aluminum ratio: XRF fluorescence method; (5) Solid content: ignition reduction method, 800℃ / 1h; Wear index: abrasion tester straight tube method; (6) Average particle size: laser particle size analyzer method; grain size: SEM electron microscope analysis.

[0031] 2. Raw material specifications (weight percentage, unless otherwise stated, all industrial products) (1) Tetrapropylammonium hydroxide (TPAOH), Wokai@Sinopharm Chemical Reagent Co., Ltd., content 25%; Tetrapropylammonium bromide (TPABr), Anhui Jinao Chemical Co., Ltd., solid; Triethylamine, liquid; (2) Kaolinite: 87% kaolinite content, 85.4% solid content, average particle size 2.0 μm, quartz content 0.5%; Halloysite: 76% halloysite content, 85.4% solid content, average particle size 4.1 μm; conventional ZSM-5: 100% silicon to aluminum ratio, average particle size 3.5 μm, solid content 85.8%; (3) Montmorillonite, SiO2 content 51.2%, MgO content 4.1%, solid content 84.6%, average particle size 7.8μm; diatomite, SiO2 content 93.5%, Fe2O3 content 1.2%, average particle size 18μm, solid content 83.8%; (4) Water glass, SiO2 content 250g / L, Na2O content 88g / L; silica sol, SiO2 30%; white carbon black, SiO2 99%; tetraethyl orthosilicate, chemically pure; (5) Sodium aluminate, Al2O3 50g / L, Na2O content 100g / L; aluminum sulfate, Al2O3 145g / L; pseudo-boehmite, alumina content 66%; SB powder, alumina content 75%; concentrated ammonia 27%; sodium hydroxide, solid; sodium bicarbonate, solid; (6) Manganese nitrate tetrahydrate, cerium nitrate hexahydrate, silver nitrate, calcium nitrate tetrahydrate, ferric chloride hexahydrate, zinc chloride, titanium chloride, and copper oxide, all chemically pure; (7) Ammonium chloride, ammonium sulfate, ammonium nitrate, ammonium phosphate, diammonium phosphate, and sodium hydroxide, all of chemically pure; (8) Hydrochloric acid 36%, phosphoric acid 85%, sulfuric acid 98%, phosphorous acid, chemically pure.

[0032] Example 1 (1) Preparation of acid-extracted clay: 2000 g of kaolin was calcined at 650°C in a muffle furnace for 5 h, and the active alumina content was measured to be 12.5%. After cooling, it was placed in a stainless steel reactor, and 6 L of 3M hydrochloric acid was added. The mixture was stirred evenly, heated to 80°C, stirred at a constant temperature for 1 h, cooled to below 50°C, and 0.4 L of concentrated ammonia water was added. The pH value was 2.0, and acid-extracted clay was obtained. (2) Preparation of pre-crystallization solution: 1600 g of TPAOH (content 25%) solution, 3.8 g of cerium nitrate, 0.7 g of zinc chloride, and 18 g of boehmite (calculated as alumina) were added to a reaction kettle. After stirring for 5 minutes, 600 g of white carbon black (calculated as silica) was slowly added. Stirring was continued until the colloid maintained fluidity until the addition was completed. Stirring was continued for 2 h. The mixture was transferred to a high-pressure crystallization kettle, heated to 160 °C, crystallized for 24 h, and then cooled to room temperature to obtain a pre-crystallization solution. (3) Preparation of microspheres: Based on 2000 g of feed on a dry basis, 33 parts of the acid-extracted clay prepared in step (1), 10 parts of kaolin, 34 parts of diatomaceous earth, 20 parts of silica sol (silicon dioxide on a dry basis), 3 parts of the pre-crystallization solution prepared in step (2) and deionized water were added to a gelling tank and mixed and homogenized to obtain a mixed slurry with a solid content of 45%. The mixed slurry was spray dried to obtain microspheres with an average particle diameter of 65 μm, which were then washed, filtered and dried. (4) Calcination and crystallization of microspheres: The dried microspheres in step (3) were calcined at 980°C for 3h, and the content of active SiO2 in the calcined microspheres was measured to be 65%; 1000g of calcined microspheres, 3000g of deionized water, 80g of sodium hydroxide, and 100g of tetrapropylammonium bromide were taken and stirred for 0.5h. The mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated to 180°C, and crystallized at a constant temperature for 24h, then filtered, washed with water, and dried to obtain a crystallized product; (5) Post-treatment of the crystallized product: 500 g of the crystallized product of step (4) was mixed evenly with 68 g of ammonium phosphate and 5000 g of water, stirred at 80° C. for 1 h, filtered and washed, and a mixture consisting of 40 g of cerium nitrate, 74 g of calcium nitrate and 300 g of water was added to the filter cake, stirred evenly, and then dried and calcined at 550° C. for 3 h to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst (PC-1), in which the ZSM-5 zeolite content in PC-1 was 70%.

[0033] Example 2 (1) The preparation of acid-extracted clay is the same as step (1) of Example 1; (2) Preparation of pre-crystallization solution: 800 g of TPAOH (content 25%) solution, 0.45 g of silver nitrate, 1.4 g of titanium chloride, and then 12 g (dry basis) of boehmite were added to a reaction kettle. After stirring for 5 minutes, 400 g (dry basis) of white carbon black was slowly added. The number of revolutions of the stirring paddle was increased according to the stirring state so that the colloid always maintained fluidity until the addition was completed. The mixture was stirred vigorously for 1.5 h, transferred to a high-pressure crystallization kettle, heated to 180 °C, crystallized for 20 h, and then cooled to room temperature to obtain a pre-crystallization solution. (3) Preparation of microspheres: Based on a dry basis of 2000 g of feed, 43 parts of the acid-extracted clay prepared in step (1), 15 parts of montmorillonite, 22 parts of diatomaceous earth, 15 parts of silica sol (silicon dioxide on a dry basis), 5 parts of the pre-crystallization solution prepared in step (2) and deionized water were added to a gelling tank and mixed and homogenized to obtain a mixed slurry with a solid content of 40%. The mixed slurry was spray dried to obtain microspheres with an average particle diameter of 63 μm, which were then washed, filtered and dried. (4) Calcination and crystallization of microspheres: The dried microspheres in step (3) were calcined at 950°C for 4 hours, and the content of active SiO2 in the calcined microspheres was measured to be 61%; 1000 g of calcined microspheres, 2500 g of deionized water, 700 g of sodium aluminate solution, and 60 g of tetrapropylammonium bromide were taken and stirred for 1 hour. The mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated to 170°C, and crystallized at a constant temperature for 28 hours, then filtered, washed with water, and dried to obtain a crystallized product; (5) Post-treatment of the crystallized product: 500 g of the crystallized product of step (4) was mixed evenly with 55 g of ammonium dihydrogen phosphate and 5000 g of water, stirred at 75°C for 1 h, filtered and washed, and a mixture consisting of 65 g of ferric chloride, 55 g of manganese nitrate and 300 g of water was added to the filter cake, stirred evenly, and then dried and calcined at 550°C for 3 h to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst (PC-2), in which the ZSM-5 zeolite content in PC-2 was 65%. Example 3 (1) Preparation of acid-extracted clay: 1500 g of kaolin and 500 g of montmorillonite were calcined at 750°C in a muffle furnace for 3.5 h. The active alumina content was measured to be 18.7%. After cooling, the mixture was placed in a stainless steel reactor. 4.5 L of 4M nitric acid was added and stirred evenly. The mixture was heated to 70°C and stirred at a constant temperature for 2 h. The mixture was cooled to below 50°C and 0.6 L of concentrated ammonia was added. The mixture was stirred for 0.5 h. The pH value was 5.5. Acid-extracted clay was obtained. (2) The preparation of the pre-crystallization solution is the same as step (2) of Example 1; (3) Preparation of microspheres: Based on 2000 g of feed on a dry basis, 23 parts of the acid-extracted clay prepared in step (1), 25 parts of kaolin, 29 parts of diatomaceous earth, 21 parts of silica sol (silicon dioxide on a dry basis), 2 parts of the pre-crystallization solution prepared in step (2) and deionized water were added to a gelling tank and mixed and homogenized to obtain a mixed slurry with a solid content of 42%. The mixed slurry was spray dried to obtain microspheres with an average particle diameter of 66 μm, which were then washed, filtered and dried. (4) Calcination and crystallization of microspheres: The dried microspheres in step (3) were calcined at 1000°C for 1.5 h, and the content of active SiO2 in the calcined microspheres was measured to be 68%; 1000 g of the calcined microspheres, 3200 g of deionized water, 85 g of sodium hydroxide, and 150 g of triethylamine were taken, and stirred for 0.3 h; the mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated to 165°C, and crystallized at a constant temperature for 30 h, and then filtered, washed with water, and dried to obtain a crystallized product; (5) Post-treatment of the crystallized product: 500 g of the crystallized product of step (4) was mixed evenly with 40 g of ammonium phosphate and 5000 g of water, stirred at 65°C for 1.5 h, filtered and washed, and a mixture consisting of 45 g of zinc chloride, 48 g of copper oxide and 300 g of water was added to the filter cake, stirred evenly, and then dried and calcined at 550°C for 3 h to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst (PC-3), in which the ZSM-5 zeolite content in PC-3 was 75%.

[0034] Example 4 (1) The preparation of acid-extracted clay is the same as step (1) of Example 3; (2) The preparation of the pre-crystallization solution is the same as step (2) of Example 2; (3) Preparation of microspheres: Based on a dry basis of 2000 g of feed, 43 parts of the acid-extracted clay prepared in step (1), 10 parts of montmorillonite, 27 parts of diatomaceous earth, 13 parts of silica sol (silicon dioxide on a dry basis), 7 parts of the pre-crystallization solution prepared in step (2) and deionized water were added to a gelling tank and mixed and homogenized to obtain a mixed slurry with a solid content of 46%. The mixed slurry was spray dried to obtain microspheres with an average particle diameter of 66 μm, which were then washed, filtered and dried. (4) Calcination and crystallization of microspheres: The dried microspheres in step (3) were calcined at 990°C for 2h, and the content of active SiO2 in the calcined microspheres was measured to be 63%; 1000g of calcined microspheres, 2300g of deionized water, 850g of sodium aluminate solution, and 80g of triethylamine were taken and stirred for 0.6h. The mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated to 185°C, and crystallized at a constant temperature for 25h, then filtered, washed with water, and dried to obtain a crystallized product; (5) Post-treatment of the crystallized product: 500 g of the crystallized product of step (4) was mixed evenly with 58 g of ammonium dihydrogen phosphate and 5000 g of water, stirred at 70°C for 1 h, filtered and washed, and a mixture consisting of 15 g of silver nitrate, 65 g of titanium chloride and 300 g of water was added to the filter cake, stirred evenly, and then dried and calcined at 550°C for 3 h to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst (PC-4), in which the ZSM-5 zeolite content in PC-4 was 66%.

[0035] Example 5 (1) Preparation of acid-extracted clay 1000 g of kaolin and 1000 g of halloysite were calcined at 850°C in a muffle furnace for 1.5 h. The active alumina content was measured to be 25.5%. After cooling, the mixture was placed in a stainless steel reactor. 4 L of 2M sulfuric acid was added and stirred evenly. The mixture was heated to 60°C and stirred at a constant temperature for 3 h. 0.3 L of concentrated ammonia was added and stirred for 0.5 h. The pH value was 2.5, and acid-extracted clay was obtained. (2) The preparation of the pre-crystallization solution is the same as step (2) of Example 1; (3) Preparation of microspheres: Based on 2000 g of dry basis, 38 parts of the acid-extracted clay prepared in step (1), 5 parts of water glass, 34 parts of diatomaceous earth, 18 parts of silica sol (silicon dioxide on a dry basis), 5 parts of the pre-crystallization solution prepared in step (2) and deionized water were added to a gelling tank and mixed and homogenized to obtain a mixed slurry having a solid content of 48%. The mixed slurry was spray dried to obtain microspheres having an average particle diameter of 60 μm. The microspheres were washed with deionized water at 50° C. and a pH of 2-3 at a weight ratio of microspheres to water of 1:8, and then filtered and dried. (4) Calcination and crystallization of microspheres: The dried microspheres in step (3) were calcined at 1020°C for 1.5h, and the content of active SiO2 in the calcined microspheres was measured to be 69%; 1000g of calcined microspheres, 3100g of deionized water, 69g of sodium hydroxide, and 150g of tetrapropylammonium hydroxide were taken and stirred for 1.2h. The mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated to 175°C, and crystallized at a constant temperature for 20h, then filtered, washed with water, and dried to obtain a crystallized product; (5) Post-treatment of the crystallized product: 500 g of the crystallized product of step (4) was mixed evenly with 95 g of ammonium dihydrogen phosphate and 5000 g of water, stirred at 85° C. for 1 h, filtered and washed, and a mixture consisting of 65 g of ferric chloride, 35 g of cerium nitrate and 300 g of water was added to the filter cake, stirred evenly, and then dried and calcined at 550° C. for 3 h to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst (PC-5), wherein the ZSM-5 zeolite content in PC-5 was 75%.

[0036] Comparative Example 1 According to CN116493039A Example 2; (1) Stir 500 g of deionized water and 1190 g of aluminum sol for 1 h, add 200 g of kaolin, stir for 4 h, then add 500 g of conventional ZSM-5 molecular sieve (silicon-aluminum ratio 120), stir for 6 h, then add 24 g of 85% phosphoric acid and 75 g of cerium nitrate hexahydrate, and continue stirring for 4 h to obtain 1# slurry; add 150 g of calcium nitrate to 500 g of deionized water, stir for 2 h to obtain 2# solution; (2) Add solution 2# to slurry 1#, stir for 2 h, and then spray dry to form the sprayed microspheres. Calcinate at 550°C for 6 h to obtain a comparative microsphere cracking catalyst (D-1).

[0037] Comparative Example 2 According to CN113398982B Example 1; First, a mixture of alkali-modified pseudo-boehmite and water glass was prepared, and then ammonium dihydrogen phosphate was added for precipitation reaction, and the silica-alumina precipitate was filtered and washed. Chemical water was added to the silica-alumina precipitate for slurrying, and then conventional ZSM-5 molecular sieve (silicon-alumina ratio 100) was added, and the weight ratio of the silica-alumina precipitate to the molecular sieve was controlled to be 60:40. The slurry was performed for 2 hours to form a uniform colloid, and then spray-dried. The microspheres were calcined at 550 degrees for 3 hours to obtain a comparative microsphere cracking catalyst (D-2).

[0038] Comparative Example 3 According to CN116371458A Example 3; (1) Preparation of microspheres: According to the composition shown in Table 1 of the patent, 2000 g of dry basis was added to the colloid tank, and 1# acid-extracted clay, kaolin, diatomaceous earth, silica sol, 1# pre-crystallization liquid and an appropriate amount of deionized water were mixed and homogenized to make the solid content of the slurry 45wt%, and then spray dried to obtain clay microspheres. The microspheres were washed with 50°C deionized water with a pH of 2.5 at a weight ratio of microspheres to water of 1:8, and then filtered and dried.

[0039] (2) Calcination and crystallization of microspheres: Calcinate the microspheres at 980°C for 3 h, take 1000 g of calcined microspheres, 3000 g of deionized water, 80 g of sodium hydroxide, and 100 g of tetrapropylammonium bromide, and stir for 0.5 h. Transfer the mixture into an autoclave, heat it to 180°C, crystallize it at a constant temperature for 24 h, then filter, wash it with water, and dry it to obtain a crystallized product.

[0040] (3) Post-treatment of the crystallized product: 500 g of the crystallized product was mixed evenly with 52 g of ammonium chloride and 5000 g of water, stirred at 80 °C for 1 h, then filtered and washed, and a mixture consisting of 60 g of orthophosphoric acid and 120 g of water was added, stirred evenly, and then dried, and calcined at 550 °C for 3 h to obtain a comparative microsphere cracking catalyst (D-3).

[0041] Application Examples The in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalysts prepared in Examples 1-5 and the comparative microsphere cracking catalysts prepared in Comparative Examples 1 and 2 were used for waste plastic cracking reaction; in a 10mL micro fixed bed reactor (the amount of catalyst added was the same), the raw material was waste polypropylene + 5% polyethylene powder, the reaction temperature was 550°C, and the feed space velocity was 1.2h -1 The mass ratio of atomized water vapor to plastic powder is 0.3:1.

[0042] Table 1 Distribution of products of catalytic cracking of waste plastics As can be seen from Table 1, by using the catalyst of the present invention to crack waste plastics, ethylene, propylene and butene can be effectively produced, the triene yield is greater than 70%, the liquid aromatic content is about 89%, and the yield of low-carbon olefins is significantly higher than that of the comparative cracking catalyst. This is because the in-situ crystallized nano-ZSM-5 catalyst prepared by the present invention has a high zeolite content and well-developed mesopores, and the molecular sieve is tightly combined with the matrix by similar chemical bonds, which enhances the activity and stability of the catalyst. The catalyst is used for the catalytic cracking reaction of waste plastics. Due to the synergistic effect of high zeolite nano-ZSM-5 and metal complexes, the yields of ethylene, propylene and butene are greatly improved, and the liquid product is rich in aromatics, thereby improving the comprehensive reaction performance of the microsphere catalyst for direct cracking of waste plastics.

Claims

1. A method for preparing an in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst, characterized in that: The following steps are involved: (1) spray drying a mixed slurry consisting of clay, an additional silicon source, a pre-crystallization liquid and water into microspheres; (2) calcining the microspheres in step (1), mixing the calcined microspheres with an alkaline aqueous solution and a template to obtain a mixture, subjecting the mixture to hydrothermal crystallization, filtering, and separating, adding a phosphorus compound and a metal compound to the hydrothermal crystallization product, mixing well, and then drying and calcining to obtain an in-situ crystallized high-zeolite waste plastic catalytic cracking microsphere catalyst.

2. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 1, characterized in that: The clay in step (1) includes acid-extracted clay and natural clay; the mixed slurry includes the following raw materials in parts by weight: 5-80 parts of acid-extracted clay, 5-70 parts of natural clay, 10-70 parts of an added silicon source, and 0.5-20 parts of a pre-crystallization liquid; the solid content of the mixed slurry is 25-65%.

3. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 2, characterized in that: The clay in step (1) includes acid-extracted clay and natural clay; the mixed slurry includes the following raw materials in parts by weight on a dry basis: 10-70 parts of acid-extracted clay, 10-60 parts of natural clay, 15-65 parts of an added silicon source, and 1-18 parts of a pre-crystallization liquid; the solid content of the mixed slurry is 30-60%.

4. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 2, characterized in that: The clay is one or more of kaolin, halloysite, diatomaceous earth, bentonite, montmorillonite, attapulgite, pyrophyllite and perlite; the added silicon source is one or more of white carbon black, silicone grease, silica gel, silica sol and water glass; the metal compound is one or more of calcium, magnesium, strontium, lanthanum, cerium, titanium, iron, cobalt, chromium, silver, zinc, vanadium, copper, manganese, gallium and molybdenum compounds; the preparation method of the acid-extracted clay is: at 40-150° C., placing the clay powder in an acid solution for 0.3-8h, and then adding alkali to adjust the pH value of the system; the preparation method of the pre-crystallization solution is: uniformly mixing the template, aluminum source and silicon source, and then crystallizing at 80-250° C. for 2-48h to obtain the pre-crystallization solution.

5. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 4, characterized in that: The acid solution is one of 0.5-12M hydrochloric acid, sulfuric acid, nitric acid and orthophosphoric acid solutions, and the mass ratio of the acid solution to the clay powder is 1.5-10:1; the clay powder is clay powder calcined at 500-950°C for 0.1-8h; the alkali is ammonia water; the template is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine, triethylamine, diethylammonium and ammonia water; the aluminum source is one or more of pseudoboehmite, boehmite, sodium aluminate, aluminum sulfate, aluminum nitrate and aluminum chloride; the silicon source is one or more of white carbon black, silicone grease, silica gel, silica sol and water glass; the molar ratio of the template, aluminum source and silicon source is 0.005-0.5:1:10-150.

6. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 1, characterized in that: The alkali in the alkaline aqueous solution in step (2) is one or more of sodium hydroxide, sodium aluminate, water glass, and ammonia water; the template agent is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine, triethylamine, diethylammonium, and ammonia water; the phosphorus compound is one or more of phosphoric acid, phosphorous acid, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; and the metal compound is one or more of lanthanum, cerium, titanium, iron, cobalt, silver, zinc, vanadium, and copper compounds.

7. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 1, characterized in that: After calcination, SiO2 in the microspheres reacts with OH in an alkaline aqueous solution. - The molar ratio of SiO2 to template in the microspheres after calcination is 1:0.01-1.0; the mass ratio of the metal compound calculated on a dry basis and P2O5 of the product after hydrothermal crystallization to the phosphorus-containing compound and metal oxide is 1:0.005-0.1:0.01-0.15; the metal compound is one or more of calcium, magnesium, strontium, lanthanum, cerium, titanium, iron, cobalt, chromium, silver, zinc, vanadium, copper, manganese, gallium, and molybdenum compounds.

8. The method for preparing in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 1, characterized in that: The microspheres in step (2) are calcined at 500-1200°C for 0.5-8h; the hydrothermal crystallization is at 100-250°C for 5-40h; and the calcination of the crystallized product is at 400-700°C for 0.5-4h.

9. An in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the in-situ crystallized high zeolite waste plastic catalytic cracking microsphere catalyst according to claim 9 in catalytic cracking of waste plastics.

Citation Information

Patent Citations

  • Catalyst for preparing low-carbon olefin through catalytic cracking of waste plastics and preparation method of catalyst

    CN113398982A

  • A catalyst for the catalytic cracking of waste plastics to produce low-carbon olefins and its preparation method.

    CN113398982B

  • Method and device for producing olefin through catalytic cracking of waste plastics

    CN116240042A

  • High zeolite nanocrystallization ZSM-5 microsphere catalyst and preparation method thereof

    CN116371458A

  • Catalytic cracking catalyst and preparation method thereof

    CN116371459A

Cited By

  • Preparation method of catalyst for waste plastic cracking

    CN121892199A